AKTIVITAS ANTI JAMUR EKSTRAK KULIT KAYU Lannea coromandelica UNTUK MENGHAMBAT PERTUMBUHAN JAMUR PELAPUK KAYU Auricularia auricula- judae: Antifungal activity test of Lannea coromandelica tree bark extract to inhibit the growth of Auricularia auricula-judae - Ayudya, Windy; Rusman, Diva Amanda; Taskirawati, Ira; Arisandi, Heru; Haspian, Haspian; Musdalipa, Musdalipa (PERENNIAL, 2022)
Increased attention to the environment causes the need for alternative preservatives to replace synthetic preservatives. Using plant extracts containing antifungal compounds can be an alternative to reducing the use of wood preservative chemicals. This study aimed to analyze the efficacy of the bark of Lannea coromandelica against the rot fungus Auricularia auricula-judge and to obtain an adequate concentration of preservative which can later be used as a natural preservative in wood from community forests. The method used in this research is divided into three stages. The first stage begins with the process of preparing raw materials. The second stage is to carry out the process of extracting the bark of Java. The last stage of this research is to test the effectiveness of antifungals in Java bark extract. Java bark extract was tested at various concentrations, namely 5 ppm, 10 ppm, 15 ppm, 20 ppm, and 25 ppm, and the control without extract. Each treatment was repeated five times. This study showed that Java bark extract at concentrations of 5 ppm, 10 ppm, 15 ppm, 20 ppm, and 25 ppm could inhibit the growth of the fungus Auricularia auricula-judge. It was indicated by the absence of hyphae that grew after 16 days of observation.